RISK EFFECT ON CONTRIBUTION OF PARTICIPANTS IN SHARIA INSURANCE INDONESIA - Istiqomah, Anisa; Gati, Vidia (Universitas Airlangga, 2020)
This study aims to prove the effect of operational costs, investment returns, claims and minimum risk-based tabarru' funds partially and simultaneously on the contribution of Islamic general insurance in Indonesia 2015-2018. This study uses a quantitative approach with secondary data in the form of publication of annual Islamic financial statements and sample selection using a purposive sampling technique. The amount of data is 11 companies with observations over four years to obtain 44 observational data used as samples in this study. The technique used is regression analysis using a fixed effect model (FEM) panel data. The results illustrate that partially, minimum variable costs based on operational risk, claims, and tabarru' funds have a significant positive effect on participant contributions. Thus proving that the higher the minimum operational costs based on claims, and tabarru' 'will influence the determination of participant contributions. As for investment returns, it has no effect on determining participant contributions because funds can be allocated to increase assets. Simultaneous statistical test results from operational costs, investment returns, claims, minimum risk-based funds are influenced by participant contributions. This research suggestion should be that Islamic general insurance companies can conduct regular audits on the use of operational costs to make it more efficient so that the allocation of contribution costs can be directed towards the growth of assets or minimum risk-based tabarru' funds of the company.Keywords: Contribution, Islamic insurance, Participant, Risk-based, Tabarru' funds